STUDI TENTANG MOTIF UKIRAN TRADISIONAL RUMAH GADANG TUANKU ALAM PUTIAH DI KECAMATAN MATUR, KABUPATEN AGAM - RIZKY PRANATA, Dr. Ramalis Hakin, M.Pd., Drs. Efrizal, M.Pd. (Serupa The Journal of Art Education, 2017)
The purposes of research are describing: 1) name wood carving 2) form of wood carving 3) placement wood carving 4) meaning traditional wood carving on the Rumah Gadang Tuanku Alam Putiah. Theory that used are theory about Rumah Gadang, traditional wood carving, decorative Minangkabau.This research using qualitative method with descriptive approach. Type of data are primary and secondary data which the source of primary data is getting directly from informan statements while secondary data from the books and study literature, data are collecting through observation, interview, and documentation.Kata Kunci: Nama, Bentuk, Penempatan, dan Makna Motif Ukiran